The Important Role of the Land Bank Concept in Perspective Land & Agrarian Law in Indonesia - Yahman Yahman (Universitas Islam Sultan Agung, 2023)
This study aims to determine the laws and regulations closely related to land bank regulations and how to harmonize land bank regulations in UUCK and Land Bank RPP against these laws and regulations. The research method used is normative legal research with a qualitative approach. This research refers to the Statute Approach to analyze laws and regulations related to Land Bank regulations and analyze the harmonization of Land Bank regulations against other laws and regulations, especially in the Land and Spatial Planning field. The results of this study are related to the rules and regulations on the implementation of land banks, among others, namely, Act No. 5 of 1960 concerning Basic Regulations of Agrarian Principles, Act No. 41 of 2009 concerning Protection of Sustainable Food Agricultural Land, Act No. 2 of 2012 concerning Land Acquisition for Development in the Public Interest, Act No. 26 of 2007 concerning Spatial Planning, Government Regulation of the Republic of Indonesia Number 11 of 2010 concerning the Control and Utilization of Abandoned Land, Presidential Regulation Number 86 of 2018 concerning Agrarian Reform, and there is harmonization and disharmonization of the articles of Land Bank regulation in the UUCK and Land Bank RPP against several other related laws. Regarding the practice of land banks, the Government needs to view cumulative justice, which lies in the equal opportunities that all people have to own Land, especially landless farmers, through land redistribution, the flagship program of land banks.